If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(y + 85) = 40 Reorder the terms: -8(85 + y) = 40 (85 * -8 + y * -8) = 40 (-680 + -8y) = 40 Solving -680 + -8y = 40 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '680' to each side of the equation. -680 + 680 + -8y = 40 + 680 Combine like terms: -680 + 680 = 0 0 + -8y = 40 + 680 -8y = 40 + 680 Combine like terms: 40 + 680 = 720 -8y = 720 Divide each side by '-8'. y = -90 Simplifying y = -90
| 0=x^2+49 | | -200+x=-94 | | 4(y-5)+3=35 | | tan37=x/10 | | K-838/4=30 | | 9(x-5)+5x=7(2x+4)-8 | | 20/3n=4 | | -(x-2)=4x+2 | | Y-(-41)=108 | | x+5+2x=29 | | 9x^2+1=-15 | | 30(q+2)=990 | | -4(2w-8)=4-12w | | 1=3(g-14)-5 | | 1/6v=-7 | | 4(x-5)/2=? | | 67-5x=-75 | | 5(x)=20+3(x) | | 6r^2+6r-36=0 | | 7x+41+3x-1=180 | | 67-(-5x)=-75 | | 25(j+6)=750 | | .5x+3=2(x-2.5) | | -4(m+3)=23 | | 7r-2(6r-5)=20 | | N/-1=13 | | m+1.02=9 | | 7-x=-1+3x | | 10(h+35)=540 | | 1.75=0.2m | | 3(37+-8y)+2y=1 | | 5/v=11/13 |